Intended and unintended knowledge spillovers in innovation - Kornelius Kraft; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Firms can use different sources of external knowledge for developing and implementing innovations. Some knowledge is provided deliberately by the source and constitutes intended knowledge spillovers, e.g., knowledge disclosed in publications or patent files. Other sources represent unintended knowledge spillovers, such as reverse engineering of technologies or hiring workers from other firms. Based on data from the Community Innovation Survey, this paper analyses the role of different types of intended and unintended knowledge spillovers for innovation output at the firm level. Among intended knowledge spillovers, using knowledge from patents shows the strongest link to innovation output, particularly in case of product innovations with a high degree of novelty (world-first innovations). Knowledge from publications is not associated with a significantly higher innovation output. Among unintended spillovers, both reverse engineering and hiring of workers positively contribute to innovation output of firms, with stronger effects for reverse engineering. Interestingly, there is a strong link between reverse engineering and process innovation output (unit cost reduction), which reflects the fact that firms using this knowledge source operate in a market environment characterized by high price competition, which incentivizes an innovation strategy based on cost efficiency.
Keywords: O31; O33; D83; 330; Knowledge sources; innovation output; intended knowledge spillovers; unintended knowledge spillovers; reverse engineering